Accommodation Communication in Communication Culture Students Year Teaching 2021/2022 Pondok Al-Muayyad Islamic Boarding School in Surakarta - Ashfiya Nur Atqiya; Pawito; Andrik Purwasito (Journal of Social Interactions and Humanities, 2022)
Occupy a new place need accommodation communication. Accommodation communication is a method individuals adapt behavioral communication with individual another. Every year Cottage Al- Muayyad Islamic Boarding School in Surakarta received Students new. Studies this review about how accommodation communication Students Year Teaching 2021/2022 Pondok Al- Muayyad Islamic Boarding School, Surakarta. Study this with descriptive qualitative in form studies case use Interview for collect data. Engaging two mercy informant with differentiate type gender , level school , age and origin different areas. Then , ccommodation communication that takes place between Students new studied with Accommodation Communication Theory (CAT) developed by Howard Giles. Accommodation Students is convergence and divergence. Stratgy communication used _ are approximation strategy and interpretability strategy. The motive used is an affective motive accommodation cooperative.